Novel SOX10 Mutations in Waardenburg Syndrome: Functional Characterization and Genotype-Phenotype Analysis - Thongpradit, Supranee; Jinawath, Natini; Javed, Asif; Jensen, Laran T.; Chunsuwan, Issarapa; Rojnueangnit, Kitiwan; Tim-Aroon, Thipwimol; Lertsukprasert, Krisna; Shiao, Meng-Shin; Sirachainan, Nongnuch; Wattanasirichaigoon, Duangrurdee (Frontiers in Genetics, 2020)
Waardenburg syndrome (WS) is a prevalent hearing loss syndrome, concomitant with focal skin pigmentation abnormalities, blue iris, and other abnormalities of neural crest-derived cells, including Hirschsprung’s disease. WS is clinically and genetically heterogeneous and it is classified into four major types WS type I, II, III, and IV (WS1, WS2, WS3, and WS4). WS1 and WS3 have the presence of dystopia canthorum, while WS3 also has upper limb anomalies. WS2 and WS4 do not have the dystopia canthorum, but the presence of Hirschsprung’s disease indicates WS4. There is a more severe subtype of WS4 with peripheral nerve and/or central nervous system involvement, namely peripheral demyelinating neuropathy, central dysmyelinating leukodystrophy, WS, and Hirschsprung’s disease or PCW/PCWH. We characterized the genetic defects underlying WS2, WS4, and the WS4-PCW/PCWH) using Sanger and whole-exome sequencing and cytogenomic microarray in seven patients from six unrelated families, including two with WS2 and five with WS4. We also performed multiple functional studies and analyzed genotype–phenotype correlations. The cohort included a relatively high frequency (80%) of individuals with neurological variants of WS4. Six novel SOX10 mutations were identified, including c.89C>A (p.Ser30*), c.207_8 delCG (p.Cys71Hisfs*62), c.479T>C (p.Leu160Pro), c.1379 delA (p.Tyr460Leufs*42), c.425G>C (p.Trp142Ser), and a 20-nucleotide insertion, c.1155_1174dupGCCCCACTATGGCTCAGCCT (p.Phe392Cysfs*117). All pathogenic variants were de novo. The results of reporter assays, western blotting, immunofluorescence, and molecular modelling supported the deleterious effects of the identified mutations and their correlations with phenotypic severity. The prediction of genotype–phenotype correlation and functional pathology, and dominant negative effect vs haploinsufficiency in SOX10-related WS were influenced not only by site (first two vs last coding exons) and type of mutation (missense vs truncation/frameshift), but also by the protein expression level, molecular weight, and amino acid content of the altered protein. This in vitro analysis of SOX10 mutations thus provides a deeper understanding of the mechanisms resulting in specific WS subtypes and allows better prediction of the phenotypic manifestations, though it may not be always applicable to in vivo findings without further investigations.